2022
DOI: 10.3390/ijerph19031199
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physical Activity and the Occurrence of Specific Symptoms of “Long-COVID Syndrome” in Men Aged 18–25

Abstract: The aim of this study was to assess the occurrence of non-specific symptoms of “long-COVID syndrome” depending on the physical activity undertaken resulting from the imposed forms of study (distance learning–contact learning); 136 men aged 21.5 ± 1.58 from universities educating students of medical faculties were examined. The difference between the universities was mainly due to the nature of the classes undertaken (classes remotely-hybrid form) in the period from March 2020 to February 2021. Among the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Long COVID signs and symptoms might vary by sex, age, and initial illness severity. For example, nervous system symptoms such as headaches and dizziness are more common among women, but men are more likely to have musculoskeletal system symptoms such as pain in the muscles or joints and numbness of the limbs ( 24 ). Younger patients have reported more headaches, abdominal symptoms, and anxiety/depression, and older patients were more likely to have breathing difficulties, cognitive symptoms, pain, and fatigue ( 19 ).…”
mentioning
confidence: 99%
“…Long COVID signs and symptoms might vary by sex, age, and initial illness severity. For example, nervous system symptoms such as headaches and dizziness are more common among women, but men are more likely to have musculoskeletal system symptoms such as pain in the muscles or joints and numbness of the limbs ( 24 ). Younger patients have reported more headaches, abdominal symptoms, and anxiety/depression, and older patients were more likely to have breathing difficulties, cognitive symptoms, pain, and fatigue ( 19 ).…”
mentioning
confidence: 99%
“…One such tool is the FFF. Authors relying on this indicator in their studies have demonstrated its versatility not only for one-off ongoing assessment but also for assessing changes in the training or ontogenetic process ( Milewska et al, 2016 ; Chwałczyńska, 2017 ; Chwałczyńska et al, 2018 ; Rutkowski et al, 2020 ; Chwałczyńska and Andrzejewski, 2021 ; Sojka et al, 2022 ). FFF is age- and sex-dependent and takes into account MM, which is part of lean mass.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the authors’ study of a group of students assessing the changes that occurred under the restrictions imposed by the Covid-19 pandemic, it was observed that these changes occurred in body composition components and not in body weight. In assessing these changes, it was found that the percentage of fat mass increased at the expense of lean mass ( Chwałczyńska et al, 2017 ; Rutkowski et al, 2019 ; Chwałczyńska and Andrzejewski, 2021 ; Golubnitschaja et al, 2021 ; Sojka et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, these exercises take a long time or require a specific location, and they do not solve the problem of “lack of time,” which is one of the factors that inhibit exercise [ 12 ]. In addition, the emergence of the severe acute respiratory syndrome–associated coronavirus 2 virus at the end of 2019 affected daily life worldwide, especially regarding physical activity, with reports of decreased physical activity in various countries compared with pre-coronavirus disease 2019 (COVID-19) pandemic levels [ 13 , 14 , 15 ]. Although the COVID-19 pandemic has been reported to have no effect on glycated hemoglobin in diabetic patients, there is a relationship between decreased physical activity and increased glycated hemoglobin caused by telecommuting [ 16 ].…”
Section: Introductionmentioning
confidence: 99%